2018
DOI: 10.1093/jme/tjy147
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Geographic Distribution of Host-Seeking AdultAmblyomma americanum(Acari: Ixodidae) in Florida

Abstract: The lone star tick, Amblyomma americanum, is the most commonly reported human-biting tick in the southeastern United States and is a vector for several human and livestock pathogens. Although it is endemic to Florida, little is known about the ecological preferences and current spatial distribution within the state. Using occurrence records of adult A. americanum collected between August 2015 and September 2016, a logistic regression model was used to estimate environmental associations, as well as to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…Similar modeling methods have successfully preempted tick establishment in novel ranges, for example the establishment of Ixodes scapularis in Canada [32,33], and the retrospective range expansion of I. scapularis across the eastern USA [34]. The potential distribution of A. americanum in the USA has been predicted using SDM methods [35,36,37,38], but typically only for eastern states or based on presence data at a coarse county-level spatial resolution. To the best of our knowledge, distributions of A. maculatum, A. cajennense, and A. mixtum have not been predicted for the USA using SDM methods.…”
Section: Introductionmentioning
confidence: 99%
“…Similar modeling methods have successfully preempted tick establishment in novel ranges, for example the establishment of Ixodes scapularis in Canada [32,33], and the retrospective range expansion of I. scapularis across the eastern USA [34]. The potential distribution of A. americanum in the USA has been predicted using SDM methods [35,36,37,38], but typically only for eastern states or based on presence data at a coarse county-level spatial resolution. To the best of our knowledge, distributions of A. maculatum, A. cajennense, and A. mixtum have not been predicted for the USA using SDM methods.…”
Section: Introductionmentioning
confidence: 99%
“…National and regional analyses that relied on information from various collection sources [4,5] indicate that selected species should be widely distributed in the region. Recently, Kessler and colleagues [14] developed a more spatially detailed analysis of Amblyomma americanum within the state and reported that the predicted species distribution was anticipated to be substantially more nuanced, with much of the spatial heterogeneity in the species distribution associated with landcover, temperature, and precipitation patterns, which was obscured in national-level analyses which focused on regional climatic variability.…”
Section: Introductionmentioning
confidence: 99%
“…We used georeferenced records from three years of tick collections performed from late 2015 through 2018 containing observations of adult Amblyomma americanum , Dermacentor variabilis , or Ixodes scapularis [39,40]. The initial dataset included 1956 surveys of presence or absence for each of the three species.…”
Section: Methodsmentioning
confidence: 99%
“…Temporally, these transects were repeated regularly throughout the study period (repeated surveys of each transect). Collection efforts occurred year-round to ensure all sites were sampled with the same intensity regardless of when individual species’ peak seasonal activity occurred [39,40]. The methods for collection are described in further detail elsewhere [39,40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation